Live birth rates after natural cycle versus hormone replacement therapy for single euploid blastocyst transfers: a retrospective cohort study. Issue 6 (December 2021) - Jin, Ziqi; Shi, Hao; Bu, Zhiqin; Guo, Yihong; Su, Yingchun; Song, Hui; Huo, Mingzhu; Yang, Entong; Li, Jingdi; Zhang, Yile
Abstract: Research question: Is there any difference in live birth rate between the natural cycle and hormone replacement therapy (HRT) endometrial preparation protocols for women with regular menstrual cycles undergoing their first single vitrified–warmed euploid blastocyst transfer? Design: This was a retrospective cohort study that enrolled 722 women who underwent vitrified–warmed euploid blastocyst transfer at assisted reproductive technology (ART) centre of The First Affiliated Hospital of Zhengzhou University, from January 2013 to December 2019. Univariate and multivariate logistic regression models were used to analyse the relationship between the endometrial preparation protocols and live birth rates. Stratified analyses and sensitivity analyses were performed to ensure the reliability and stability of the results. Results: A total of 722 single vitrified–warmed euploid blastocyst transfer cycles were included. Overall, the live birth rates were 50.00% (110/220) in the natural cycle group and 47.61% (239/502) in the HRT group. Multiple logistic regression analyses showed that there was no significant association (adjusted odds ratio 0.82; 95% confidence interval 0.56–1.20; P  = 0.313) between natural cycle and HRT protocols and the live birth rate. Interaction analysis showed that there was no significant difference in live birth rates between the two groups for any subgroup after adjusting for confounding factors. Conclusions: For single vitrified–warmed euploid blastocyst transfer, natural cycle and HRT endometrial preparation protocols result in similar live birth rates among women with regular menstrual cycles. Further studies are needed into the effects of endometrial preparation protocols on pregnancy outcomes.